Conic Parameterization in PG(2,25) - Emad Bakr Al-Zangana; Elaf Abdul Satar Shehab (Al-Mustansiriyah Journal of Science)
The main aim of this paper is to parameterize the conics form through the inequivalent 5-arcs in PG (2,25) using one-one correspondence property between line and conic. The inequivalent 6-arcs in PG (2,25), also have been computed with some examples.